Frog metamorphosis: a review of metamorphic stages, developmental progression, and influential factors - Shahrum Nizam, Khairunnisa; Ismail, Nor Azliza; Farinordin, Farah Ayuni; Mohd Izam, Nur Amalina (Universiti Teknologi MARA (UiTM), 2023)
Frog (Order: Anura) is the most diverse, diversified, and ubiquitous of the three extant amphibian orders under the class Amphibia. They are distributed across the globe, with the exception of the polar regions, some marine islands, and very dry deserts. The life cycle of a frog is a fascinating event in which they go through an incredible transition known as 'metamorphosis' as they grow from frogspawn to adult frogs. Although extensive research has been done on the life cycle and metamorphosis of frogs, there is little comparative information on different variances in its unique transformation traits during evolution among the families and factors influencing these transformational processes. This review focuses on identifying the metamorphosis process in distinguished frog families by comparing stages of development, morphological and physiological changes, and the factors that influence their growth or metamorphosis and timing. The study was conducted by reviewing about 130 sources of previous scientific publications, primarily accessible through online journal and article publishing platforms or databases such as Google Scholar, Scopus, and Web of Science. Subsequently, significant differences within the frog families have been recorded. Hormones, environmental cues, and the availability of resources are all intrinsic and extrinsic variables that influence these developmental stages. Further studies are needed to undertake a comprehensive study that includes complete monitoring of frog metamorphosis and development at all phases. This would provide important insights into the genetic and molecular factors that control the timing and success of frog metamorphosis, which could also improve the understanding of the delicate interplay between environmental cues and developmental processes by doing such studies.